Motivational profile: understanding academic performance as a criterion of cost, expectancy for success and task value - Conway, Gail D.; Ouano, Jerome A. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Using a descriptive study design, this research determined how task effort cost, emotion cost, loss of valued alternatives, outside effort cost, social cost, economic cost and sunk cost along with expectancy for success and task value formed a criterion related profile associated with higher academic performance. It used the survey method to gather data from a total of 226 college students enrolled in a high-stake math class. Findings revealed three significant criterion related factors, namely expectancy for success, task value and sunk cost. This motivation profile indicated a high score in expectancy for success, an even higher score in task value and a low score in sunk cost, Β = .43, t(224) = 7.22, p < .001. Relationships for the first two confirmed the hypothesized direction while the last one illustrated an inverse connection. Results are discussed in light of the expectancy-value-cost theory and existing studies. This research has implications on the nuances of the construct of cost, on pedagogic relevance, and on school and counseling psychology.